KINERJA PENGELOLAAN JALAN DAN JEMBATAN DALAM PERSPEKTIF PELAYANAN PUBLIK PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG PROVINSI BANTEN TAHUN 2017 - Arfindy Sri Nur; Ahmad Sihabudin; Ace Hasan Syadzily (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2019)
This research discusses how to manage roads and bridges in public services. This study aims to analyze the performance of road and bridge construction in public services at the Banten Provincial Public Works and Spatial Planning (PUPR) Office in 2017. The theory used in this study discusses the performance appraisal model according to Dwiyanto in pasolong (2010: 178), quality service, Responsiveness, Responsibility, and Accountability. The research method used is qualitative. Data collection techniques used were interviews and documentation. The results of this study are that the performance of the Banten Province PUPR Service can be approved quite well about there are several developments on roads and bridges such as the failure of development and delays, the work carried out is in accordance with the vision and mission of the organization. The Banten Provincial PUPR Office tried to respond in the settlement of the community lawsuit, the compilation of development planning responses was made, the construction and maintenance of the road and development was carried out according to the budget and carried out in stages. Factors that hamper performance such as facilities and infrastructure that are still lacking such as heavy equipment in the construction / maintenance of roads and bridges if used in time related to activities that can help and slow down materials, amount and quality of human resources in terms of PUPR service staff or service providers, people's perceptions of consistency, and natural nature. The efforts of the PUPR Service to improve community licensing in managing roads and bridges Speed up the arrival of material stocks, increase the number of heavy equipment, improve the quality and advantages of human resources, and implement E-Government by improving the SIAP PUPR application system that is available for community needs in response to complaints / complaint. Kata Kunci : Kinerja, Pengelolaan jalan dan jembatan, Pelayanan publik.